A 3D Snapshot of Crustal Breakup Deduced From Seismic Analysis of the Tip of the NW South China Sea. Issue 6 (1st June 2022) - Chao, P.; Manatschal, G.; Chenin, P.; Zhang, C.; Ren, J.; Peng, X.; Zheng, J.
Abstract: Based on a high‐resolution seismic reflection data set, we describe and map rift domains at the tip of the V‐shaped NW‐South China Sea (NW‐SCS) Basin. We compare our rift domain map with seismic refraction, magnetic and gravity field data, and previously mapped Continent‐Ocean Boundaries (COB). We also define and map syn‐breakup sedimentary and magmatic sequences across the sediment‐rich NW‐SCS, which enables us to reconstruct the tectono‐stratigraphic evolution of the area. This work enables us to describe and discuss the 3D architecture and nature of the crust at the tip of the NW‐SCS, investigate how extensional and magmatic processes interacted during the breakup, and propose a kinematic model for late rifting, breakup, and finally stalling of the seafloor spreading system. This study provides exceptionally well‐documented insights into the spatial and temporal evolution at the tip of a so‐called "rift propagator, " and enables us to show that breakup in the NW‐SCS may rather correspond to a "retrogrador, " in which the extension zone retreats due to the reorganization of a failing rift system. Key Points: We highlight for the first time the 3D crustal structure of the tip of the NW‐South China Sea (NW‐SCS) V‐shaped basin Based on the architecture of sedimentary and magmatic deposits, we propose a 4D model for its breakup phase Proposition of a new retrogrador breakup model for the NW‐SCS